IMPLEMENTATION OF VIDEO MEDIA IN DEVELOPING RELIGIOUS AND MORAL VALUES IN EARLY CHILDREN - Dinul Akbar Nasution; Tien Rafida; Ahmad Syukri Sitorus (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
Religious and moral values are very important to be instilled in children from an early age. Al Washliyah Kelambir Lima Integrated Islamic Kindergarten (TK IT) has tried to handle religious and moral values in these children by using video media that they made themselves based on their needs. This study aims to look at the implementation of video media in developing religious and moral values for early childhood, monitor its development, see the advantages of this method and its shortcomings. In this study using a qualitative method which was carried out in TK IT Al Washliyah Kelambir Lima. To collect data, it is done using interview, observation, and documentation instruments. Meanwhile, data analysis uses the Miles and Huberman model where data reduction, data presentation and conclusion drawing are the main techniques. The results of the study indicate that the implementation of the video media has had a positive impact on the development of children's religious and moral values. Thus, it is concluded that the use of video media can provide benefits for developing religious and moral values for early childhood.